2013
DOI: 10.1186/1472-6963-13-335
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS-related attitudes and oral impacts on daily performances: a cross-sectional study of Sudanese adult dental patients

Abstract: BackgroundFew studies have investigated the relationships between HIV-related knowledge, fear of contagion in dental environments and Oral Impacts on Daily Performance (OIDP) among dental patients. Our objectives were to investigate the associations between HIV-related knowledge and fear of contagion in dental environments and OIDP among dental patients, and to evaluate whether those associations were modified by the frequency of dental service attendance.MethodsA total of 1262 patients (mean age 30.7 years, 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
6
1
1
Order By: Relevance
“…This shows that the demand for dental care happens when the dental disease is already at an advanced stage, which causes irritation and pain. A direct consequence of this systematic exclusion of services, extractions are outcomes that, in most cases, could be avoided …”
Section: Discussionmentioning
confidence: 99%
“…This shows that the demand for dental care happens when the dental disease is already at an advanced stage, which causes irritation and pain. A direct consequence of this systematic exclusion of services, extractions are outcomes that, in most cases, could be avoided …”
Section: Discussionmentioning
confidence: 99%
“…The adapted version of the OIDP is used in South Africa, Spain, Italy, Sweden, Thailand, Malaysia, Sudan, Peru, Brazil, and other countries, showing that there is face and content validity for different populations (3)(4)(5)(6)(7)(8)(9). Studies undertaken in Great Britain, Malaysia, Peru, Korea, and Brazil have shown construct validity and reliability of the instrument (2,8,(10)(11)(12).…”
Section: Research Involving Quality Of Life Including Oralmentioning
confidence: 99%
“…Study participants also reported that they avoid seeking dental services in non-specific places for the public with HIV/AIDS, for fear of not having the necessary care to sterilize the equipment and thus be able to transmit the virus. This demonstrates the need for communication to the population about effective measures to control the transmission of this infection, which should be adopted in dental offices (36) . There is a high probability that participants in the present study were able to access dental services on a regular basis, only from their insertion in the specialized service for HIV/AIDS, when they did not present a good oral condition, a fact similar to that demonstrated in another research (17) .…”
Section: Discussionmentioning
confidence: 99%